The Kerry-Lugar Bill: Dilemma of Trust and Mistrust between Pakistan and USA - Bakht, Asma; Ejaz, Ahmad (Annals of Human and Social Sciences, 2023)
The Kerry-Lugar Bill is intended to pursue these goals with assistance from Pakistan's ailing government, as the Trump administration appears set to engage effectively with the South Asian area, at least in the near run. The basic objectives of this paper is to find out the pros and cons of Kerry-Lugar Bill for Pakistan under the critical situation war on terroir. The study will follow the critical qualitative approach toward the KLB, its background, US approach toward Pakistan in the war of terroir. Critics say the aid clearance represents a sell-out of national sovereignty, while the Pakistani administration celebrates it as a diplomatic victory. They highlight what they call 'degrading' conditions that Pakistan may have to meet in order to get help. The United States Congress might not accept anything less than a substantial increase in its aid budget, considering its track record of aid distribution. As long as there is a converging of interests, the stipulations on the aid will likely remain in place. Additionally, this article highlight, Despite significant ideological differences on the subject of war on territory, this shows how the KLB Act helps to keep the peace between Pakistan and the United States.